The effect of quick response manufacturing in factory layout: Assessment using Witness software - Yusoof, M. Y. M.; Nik Mohamed, N. M. Z.; Nelfiyanti, .; Hadi, M. Z. I. A. (IOP Publishing, 2021)
Nowadays, in a new era of industrial revolution 4.0, there are still many manufacturing companies that tend to neglect the knowledge of optimizing the factory layout. By doing so, the productivity can be increase and lessen the burden of the operator while making sure the quality and also the number of products are also at optimum. The objective of this study is to conduct an analysis on the actual arrangement assembly line using witness software based on QRM in V model assembly and also to propose a new arrangement of the assembly line using Witness software. The data has been collected and recorded through some observation during the visit to X Company. The current layout of the V model assembly line is simulated in the Witness software to get its actual process, percentage of idle, and also the setup time. The software is also used for the new improvement of the assembly line layout to get the comparison for the current layout and after the improvement. Based on the current result, there is some station that has a high percentage of blockage occur in the layout and after the improvement, the percentage of blockage has been reduced which help in increase the production of the model per day. The data that has been recorded from the current is compared with the data after the improvement has been made to the assembly line.